Comparison of Carbopol and Carboxymethyl Cellulose as Thickener on Making Bioethanol Gel - Ariyani, Sukma Budi; Supriyatna, Nana (Biopropal Industri, 2013)
Bioethanol gel is a new form of liquid bioethanol that has been given a thickening agent. This type of bioethanol is believed could make its transportation and utilization safer. This study aimed to compare the carbopol and carboxymethyl cellulose as thickener agents and to characterize the bioethanol gel produced. In this research, carbopol and carboximethyl used for making bioethanol gel were1.5, 3, 4.5 and 6 g. Then flame color, length of flame and viscosity were tested. The best bioethanol gel produced obtained on the addition of carbopol 6 g. Its characteristics were clear white color, the flame color is blue reddish, length of flame per 5 g is 5 minutes 17 seconds, and viscosity 1,380,000 cP. The boiling water test result on 100 ml of water by using 15 g of bioethanol gel takes 16 minutes.